Studies on trimethoprim: Hydroxypropyl-β-cyclodextrin: Aggregate and complex formation - Garnero, Claudia (2010)
The present study is focused on the characterization of the interaction between trimethoprim, a dihydropteroate synthesase inhibitor, and hydroxypropyl-β-cyclodextrin (HP-β-CD) in aqueous solution and solid state. The freeze-drying method was used to prepare solid complexes, while simple blending was employed to obtain physical mixtures. The phase solubility was AN type, and demonstrated that trimethoprim solubility was significantly increased upon complexation with HP-β-CD. Conductivity experiments showed the presence of aggregates that explains the type profile for the solubility isotherm. The critical concentration for the aggregate formation was determined to be 69.3 mg/ml for pure HP-β-CD and 117.7 mg/ml in the presence of trimethoprim. Nuclear magnetic resonance spectroscopy provided evidence of trimethoprim:HP-β-CD molecular interaction in solution. Moreover, the complex was characterized in solid stated using Fourier-transform infrared spectroscopy (FT-IR) and scanning electron microscopy (SEM). The use of differential scanning calorimetry (DSC) and thermogravimetric analysis (TGA) showed that the thermal stability of the drug is enhanced in the presence of HP-β-CD.